Analysis of Psychological and Pedagogical Training in the Process of Training in Higher Educational Institutions of the Republic of Kazakhstan and the People’s Republic of China (Journal of Educational Sciences, 2022)
The processes of globalization and international integration have been the subject of much researchin the field of higher education in many countries. The desire to integrate teacher education has becomeone of the main trends in modern international theory and practice of teacher education. The purpose ofthis article is to analyze the professional training of students of psychological and pedagogical specialties of universities in China and Kazakhstan by comparing work plans, credits and hours devoted to thestudy of individual sections and disciplines. Studies of integration between the Republic of Kazakhstanand the People’s Republic of China show that there is quite a wealth of experience in the developmentand reform of teacher education between the two countries.The authors of this article analyzed the ideas, goals, curricula, and teaching methods in China andKazakhstan. Integration processes in the field of education between the Republic of Kazakhstan and thePeople’s Republic of China have a market orientation, focus on organizational innovation in education. The reform of education integration in Kazakhstan in the future should be focused on three aspects:improvement of plural cooperation, mutual management system of teachers’ education and strengthening of this link after the end of teaching activity. The PRC is actively developing models of professionallearning communities aimed at teacher training.The article makes an attempt of comparative analysis of psychological and pedagogical training inthe process of training in higher educational institutions of RK and PRC. Internationalization and integration are the components of the modern process of higher education, contributing to its competitivenessand approaching to the best international practices.Key words: integration, education, psychological and pedagogical training, higher education; reflexion.